The lean strategy : using lean to create competitive advantage, unleash innovation, and deliver sustainable growth - Ballé, Michael, 1965-; Jones, Daniel T. (McGraw-Hill Education, 2017)
Addressing popular misconceptions about the basics of lean/TPS; this groundbreaking book shows the true purpose of the tools; methods; and attitudes that leverage the intelligence of every employee doing the work. --